Neurometabolic Disorders of the Newborn. Issue 4 (August 2018) - Mankad, Kshitij; Talenti, Giacomo; Tan, Ai Peng; Gonçalves, Fabrício Guimarães; Robles, Carlos; Kan, Elaine Y. L.; Siddiqui, Ata
Abstract : Abstract: There is an extensive and diverse set of medical conditions affecting the neonatal brain within the spectrum of neurometabolic disorders. As such, their clinical presentations can be rather nonspecific, and can often mimic acquired entities such as hypoxic-ischemic encephalopathy and sepsis. Similarly, the radiological findings in these entities can also be frequently nonspecific, but a more detailed analysis of imaging findings (especially magnetic resonance imaging) alongside the relevant clinical details can be a rewarding experience, thus enabling a timely and targeted diagnosis. Early diagnosis of an underlying neurometabolic disorder is vital, as some of these entities are potentially treatable, and laboratory and genetic testing can be precisely targeted. Further, their detection helps with counselling families for future pregnancies. We present a review of neurometabolic disorders specific to the newborns with a focus on how neuroimaging findings match their clinical presentation patterns.